Distribution of Al, Fe, and Si oxides in three soil orders in dryland of Aceh Besar, Indonesia. (December 2019) - Sufardi; Arabia, T; Khairullah; Karnilawati; Nurnikmat, T Z
Abstract: The Al, Fe, and Si fractions in the soil are often associated with silicate minerals and hydroxide oxide fractions. The composition of these minerals in the soil is influenced by the degree of weathering and soil development. This study investigated the content and distribution of Al, Fe, and Si oxides in three soil orders (Inceptisols, Ultisols, and Oxisols) on dryland in Aceh Besar, Indonesia. Soil samples were collected in the layers of soil horizon of each profile. The content of Al, Fe, and Si in the soil was extracted with two selective solvents, namely sodium dithionite-citrate solution to determine the forms of Al, Fe and Si free and ammonium-oxalate to determine the forms of Al, Fe, and Si amorphous. The content of Al, Fe, and Si in the extract was measured by AAS. The results showed that the content and distribution of Al, Fe, and Si oxides of soil in the dryland of Aceh Besar varied between soil orders and also differed between horizons. The dithionite-extractable Al ranged from 0.02% to 13.14%, the dithionite-extractable Fe ranged from 1.01% to 4.08%, while the dithionite-extractable Si ranged from 0.62% to 4.29%. The oxalate-extractable Al ranged from 2.09% to 6.44%, the oxalate-extractable Fe ranged from 0.23% to 1.62%, while the oxalate-extractable Si ranged from 1.37% to 18.5%. The content of Fe oxides varied from 0.42% to 3.64%, while the index of crystallinity of Fe ranged from 0.11 to 0.79. The distribution of Al, Fe, and Si oxide at several soil orders on dryland Aceh Besar district was very diverse. The distribution of Al- and Fe-oxide were not consistent with the depth of the soil, while Si-oxide tends to decrease with increasing soil depth. The sequential of Fe crystallinity index from low to high is Oxisols < Ultisols <Inceptisols which means that Oxisols is more developed than Ultisols and Inceptisols.